PENINGKATAN KESEHATAN PERSENDIAN MELALUI SENAM PENCEGAHAN OSTEOARTRITIS DI KEC. GUNUNG MALIGAS - Muliati, Muliati; Marolop Parlindungan Napitu; Isa Harpika Br. Ginting; I Ngurah Gede Verar Fujastawan; Margaretha Togatorop (Yayasan Nusantara Hasana Berdikari, 2024)
Osteoarthritis is a degenerative disease commonly experienced by the community, especially among the elderly, which can reduce quality of life due to pain and limited mobility. This community service activity aimed to improve community knowledge, skills, and awareness in maintaining joint health through osteoarthritis prevention exercise in Gunung Maligas District. The methods used included socialization, exercise training, mentoring, and evaluation. The results showed an increase in community understanding of osteoarthritis as well as their ability to perform preventive exercises. In addition, exercise groups were formed to ensure program sustainability. The activity also had a positive impact, including a reduction in joint pain complaints among participants. Therefore, osteoarthritis prevention exercise can be an effective strategy to improve community joint health sustainably.